2012
DOI: 10.1088/0268-1242/28/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vacuum annealing on the optical and electrical properties of p-type copper-oxide thin-film transistors

Abstract: We have investigated the effects of vacuum annealing on the optical and electrical properties of the p-type copper-oxide thin-film transistors (TFTs). The vacuum annealing of the copper-oxide thin-film was performed using the RF magnetron sputter at various temperatures. From the x-ray diffraction and UV-vis spectroscopy, it is demonstrated that the high-temperature vacuum annealing reduces the copper-oxide phase from CuO to Cu 2 O, and increases the optical transmittance in the visible part of the spectrum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
4
31
0
2
Order By: Relevance
“…These band gap values match with the reported values. 1,13 The optical transmission for the Cu 2 O thin films (grown on glass substrates) observed in the present study is 72% at 600 nm.…”
mentioning
confidence: 47%
“…These band gap values match with the reported values. 1,13 The optical transmission for the Cu 2 O thin films (grown on glass substrates) observed in the present study is 72% at 600 nm.…”
mentioning
confidence: 47%
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…In 2012, Sohn et al presented a p‐type Cu 2 O TFT by reducing the as‐deposited CuO channel at high temperature . The CuO film was deposited at room temperature by RF sputtering using a Cu target, followed by subjecting the as‐deposited film to various annealing temperatures in vacuum for 7 min.…”
Section: Performance Of P‐type Oxide Thin‐film Transistorsmentioning
confidence: 99%
“…75,298,299 Moreover, doping of n-type metal oxide semiconductors has enabled the demonstration of p-type TFTs based on P-and N-doped ZnO NW, 259,300 as well Ga 2 O 3 :Zn. 70 Among all the reported p-type metal oxide semiconductor TFTs, [70][71][72][73][74][75]79,[280][281][282][283][284][285][286][287][288][289][290][291][292][293][294]300 only few devices have been fabricated on flexible substrates. 36,79,257,267,272,273,285,289 This is mainly due to the high deposition and annealing temperatures (typically !200 C) that are required, which are incompatible with flexible temperature-sensitive substrates.…”
Section: A P-type Metal Oxide Semiconductorsmentioning
confidence: 99%